WATERFLOOD SUSCEPTIBILITY OF NGRAYONG SANDSTONE RESERVOIR IN “X”-WELL, XYZ FIELD, EAST JAVA (WATERFLOOD SUSCEPTIBILITY PADA RESERVOIR BATUPASIR NGRAYONG DI SUMUR-“X”, LAPANGAN XYZ, JAWA TIMUR) - Rosidelly Rosidelly (Testing Center for Oil and Gas LEMIGAS, 2017)
Antiklinorium structures that are spreading in the area of Rembang Zone along the Central Java to East Java reflect oil traps that lay under the surface. The oil fields have been exploited since the time of the Dutch occupation leaving the water cut at above 95%. Interpretation of reserves and production forecasts made by many researchers conclude that the remaining oil is still in the range of 50% (OOIP). To overcome the problem, the Government recently encouraged researchers to conduct a comprehensive review in terms of enhanced oil recovery with the goal of increasing the oil recovery in this zone by as much as possible. The XYZ-oil field in the Rembang Zone has a widely spread reservoir sandstone in the border area of the Central Java - East Java. Reservoir rocks in this area contain calcareous and silty matrix. Clay minerals mineral that is easily removed by fluid flow so that it would create problems during the oil production process. The composition of injection water collected from several wells can also easily form slugs and scale as indicated by the occurrence of crude oil and bacteria that behave as a very corrosive substance that tends to facilitate the creation of production and equipment damage. This study conducted an experiment in enhanced oil recovery using waterflooding. To avoid the occurence of non-Darcy flow, critical velocity analysis was conducted obtaining a value of 37.6 ft/day. This velocity is defi ned as a maximum injection velocity of the water displacement in this waterflooding experiment. Based on the waterflooding experiment of X-Well in the laboratory, the injection of oil using injection water without additives led to an increase in oil recovery of 0.77% Pore Volume (%PV), while the displacement of injection water added with additives resulted in an increase in oil recovery by as much as 1.31%PV. Struktur-struktur antiklinorium yang terbentang di daerah Zona Rembang Jawa Tengah hingga Jawa Timur mencerminkan perangkap minyak yang berada di bawah permukaan. Lapangan-lapangan minyak ini sudah dieksploitasi kandungan minyaknya sejak jaman Belanda dimana pada saat ini kandungan water cut sudah di atas 95%. Dari interpretasi cadangan dan produksi yang dilakukan oleh banyak peneliti, diperkirakan minyak yang tersisa masih berada di kisaran 50% (OOIP). Untuk mengatasi hal tersebut akhirakhir ini pemerintah mendorong para peneliti agar melakukan kajian pada lapangan-lapangan minyak di zona tersebut dalam rangka peningkatan perolehan minyak secara menyeluruh dengan target perolehan minyak yang sebesar-besarnya. Lapangan minyak XYZ yang berada di Zona Rembang mempunyai reservoar batupasir yang penyebarannya cukup luas di daerah perbatasan Jawa Tengah – Jawa Timur. Batuan reservoir di daerah ini merupakan batupasir berbutir halus yang mengandung matrik gampingan dan lempungan. Mineral lempung hampir terdistribusi merata dengan kandungan kaolinit yang cukup tinggi (30% dari kandungan mineral lempungnya). Kaolinit merupakan mineral yang mudah terlepas oleh adanya aliran fluida sehingga akan menjadikan masalah sewaktu proses produksi berlangsung. Air injeksi dari beberapa sumur mengandung komposisi yang juga memudahkan terbentuknya slug dan scale seperti dijumpainya kandungan crude oil serta bakteri yang bersifat korosif sehingga cenderung memudahkan terbentuknya kerusakan formasi dan korosi pada peralatan pemboran maupun produksi.Sesuai dorongan pemerintah, studi ini dilakukan untuk melakukan percobaan dalam meningkatkan perolehan minyak dengan menggunakan metode waterflooding. Untuk menghindari terjadinya aliran non-Darcy dilakukan analisis Kecepatan Aliran Kritis (Critical Velocity) dimana hasilnya diperoleh = 37.6 ft/day, yang ditetapkan sebagai kecepatan pendesakan air injeksi maksimum dalam percobaan waterflooding. Berdasarkan percobaan waterflooding dalam sekala laboratorium pada Sumur-X, pendesakan minyak dengan air injeksi tanpa ditambah bahan aditif menghasilkan peningkatan perolehan minyak sebesar 0.77% Pore Volume (0.77%PV), sedang jika air injeksi ditambah bahan aditif peningkatan perolehan minyak dapat mencapai 1.31%PV.